Vliv nanočástic TiO2 a ZnO na fotokatalytické a antimikrobiální účinky silikátových nátěrů - Hochmannová, Libuše; Vytřasová, Jarmila (Chemické listy, 2010)
Silicate paints containing photocatalytically active TiO2 and ZnO nanoparticles were formulated. The photocatalytic efficiency of coatings was evaluated as a change in absorbance of Orange II solutions. The agar plate method was used for evaluation of antimicrobial properties of coatings. The effectiveness of the coatings was demonstrated using Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus bacteria and Aspergillus niger and Penicillium chrysogenum fungi. A slightly better photocatalytic effect was found in the coatings containing TiO2 nanoparticles than in those with ZnO. The antimicrobial activity of coatings containing nano-TiO2 was negligible. The silicate coatings containing 7.5 vol.% of ZnO nanoparticles showed an excellent antimicrobial activity against all tested bacteria and fungi Aspergillus niger; they partly inhibited also the Penicillium chrysogenum growth. Statistically significant differences between the control coatings and those with ZnO nanoparticles were found using the Rank-sum test.
Keywords: ultrafialové záření; statistika jako téma; Zinc Oxide; Anti-Infective Agents; Nanoparticles; Paint; Financing, Organized; Bacteria; nanočástice; Fungi; protézy a implantáty; Statistics as Topic; oxidy; Ultraviolet Rays; Equipment and Supplies; silikáty; nátěrové hmoty; houby; titan; Oxides; Silicates; Clinical Laboratory Techniques; klinické laboratorní techniky; financování organizované; oxid zinečnatý; Titanium; antiinfekční látky; Prostheses and Implants; zdravotnické prostředky